An unusual case of extensive polypoid high-grade dysplasia in Barrett's esophagus - Benites, Harold (2023)
Barrett’s esophagus (BE) is a known precursor of dysplasia and adenocarcinoma. Endoscopic resection and surgery are the techniques used to treat these kinds of lesions. However, endoscopic resection is considered the first choice for the management of superficial lesions. Dysplasia in BE most commonly appears like a flat lesion but here we describe an unusual case of dysplasia and superficial adenocarcinoma looking like an extensive polypoid lesion.